Research on the Spatial Agglomeration Characteristics of Commercial Service Facilities in the Osaka Metro Midōsuji Line Rail Transit Station Area - Wang, Zihao; Zhang, Yikang; Yao, Minfeng; Chen, Xiaomin; Zhai, Zhijunjie (MAJ - Malaysia Architectural Journal, 2025)
With the rapid development of rail transit systems in developing countries, the problems of low adaptability of commercial facilities to stations and lack of commercial vitality in rail transit station areas have gradually emerged, which in turn hinders the conversion of station passenger flow into commercial flow and is not conducive to the sustainable development of commerce. The Japanese rail transit represented by Osaka Midosuji Line can be taken as a typical representative of the study due to its early construction, high density and large passenger flow. Based on the field research of Osaka Midosuji Line and POI-based multi-source big data, this paper comprehensively applies the methods of spatial data visualization and spatial statistics to firstly classify the stations into four types, namely, residential, transportation hub, public service, and commercial service, and then summarize the spatial characteristics and agglomeration patterns of commercial facilities around each station of the line, analyze the similarities and differences in the commercial spatial structure and proportion of the commercial facilities around the stations, and deeply analyzes the main factors affecting the spatial agglomeration of commercial service facilities. It is found that different functional types of stations show different spatial agglomeration characteristics, which are mainly influenced by factors such as pedestrian accessibility and functional diversity of land within the station area. It is also found that higher commercial diversity can effectively improve the service level of the station area and better promote sustainable commercial development. Finally, optimization suggestions are made for the commercial layout strategy of developing countries’ rail transit stations.